Fast flavor oscillations of astrophysical neutrinos with 1, 2, …, ∞ crossings. Issue 7 (13th July 2021) - Bhattacharyya, Soumya; Dasgupta, Basudeb
Abstract: In the early Universe, as well as in supernovae and merging neutron stars, neutrinos have such high densities that they affect each other and exhibit collective flavor oscillations. A crucial ingredient for fast collective flavor oscillations is that the electron lepton number (ELN) distribution changes its sign as a function of direction, i.e., has a zero crossing. We present a study in two spatial dimensions and time, focussing on the fast and linear regime, and show how fast flavor oscillations depend on the ELN and its crossings. We show that a large number of crossings can inhibit flavor oscillations. This may be a natural self-limiting mechanism that stabilizes the flavor content of the dense neutrino gas in a vast majority of scenarios, especially the early Universe, where the angular distributions for all flavors are very similar and crossings occur mainly due to fluctuations.